«BIG DATA» IN EDUCATION: INTERNATIONAL AND RUSSIAN EXPERIENCE - Grinshkun В.В; Zaslavskaya О.Ю (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Big data analysis and their free circulation can serve as a basis for qualitative changes, the formation of a new modern and dynamically developing education system. The article analyzes data on the educational process, which will make it possible to better assess teachers and, if necessary, make changes to the content of their training. As data for the analysis, information about the traits of the student’s character, his success in learning, and previous work experience are used. One of the significant points in terms of collecting and structuring big data in Russian education is the creation and implementation of the Moscow Electronic School project. Big data collection and analysis technologies open up great prospects for creating new positive learning experiences and highly effective expansion of lifelong learning competencies.